Strategi Manajemen Konflik Dalam Penyelesaian Sengketa Pemilihan Kepala Daerah Kota Bandar Lampung - Sinta Apriyani; Andhika Purbakala Rona (Bahasa Indonesia, 2023)
The existence of disputes in the general election process in Bandar Lampung City in 2020 indicated that the election process in Bandar Lampung City still needs to be addressed. The purpose of this study is to find out the conflict management strategy in resolving regional head election disputes in 2020 by the Bandar Lampung City Election Commission using Thomas and Kilman's theory including accommodative, avoiding, collaboration, compromise and competition. The method in this study uses descriptive qualitative. The results showed the Bandar Lampung City Election Commission to carry out an accommodative strategy by accommodating violation reports, collaboration strategies by involving Bawaslu and KY to conduct investigations and compromise strategies in accepting the Supreme Court decision to re -establish candidate pair number 3 as membership of the Mayor of Bandar Lampung Year 2020. These violations such as giving food, transportation money, empowerment of family welfare and there is the use of access to the position of husband as Mayor of the incumbent. Impacts to the process of organizing general elections in Bandar Lampung City